Te Arewhana Kei Roto i Te Rūma: An Indigenous Neo-Disputatio on Settler Society, Nullifying Te Tiriti, ‘Natural Resources’ and Our Collective Future in Aotearoa New Zealand - Simon, Hemopereki (Te Kaharoa, 2016)
This practice-research based article explores the relationship between mana motuhake and white patriarchal sovereignty in Aotearoa New Zealand, focusing on Ngāti Tūwharetoa as a case study. It seeks to find the relevance of Aboriginal academic Aileen Moreton-Robinson’s white possessive doctrine to the Aotearoa New Zealand context. In particular, it highlights the racist nature of the law and planning systems and their inadequacies to provide for hapū and iwi. It provides a key theoretical analysis regarding the nature of white patriarchal sovereignty in Aotearoa and the need of the state to appear virtuous, to continue the legacy that started with the Treaty of Waitangi to maintain this whenua as a white possessive. Lastly, the piece questions the position of Britishness within Aotearoa New Zealand and asks key philosophical questions for all about the need to find common understandings or māramatanga about our collective future as a society.